2018
DOI: 10.1177/0049475518790893
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric road traffic injuries in Lilongwe, Malawi: an analysis of 4776 consecutive cases

Abstract: This was a retrospective review of all children aged ≤16 who were treated in the casualty department at the central hospital in Lilongwe, Malawi, between 1 January 2009 and 31 December 2015. A total of 4776 children were treated for road traffic injuries (RTIs) in the study period. There was an increase in incidence from 428 RTIs in 2009 to a maximum of 834 in 2014. Child pedestrians represented 53.8% of the injuries, but 78% of deaths and 71% of those with moderate to severe head injuries. Pedestrians were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Road traffic accidents are a common cause of injury for both children and adults in sub-Saharan Africa [ 29 ]. Similar to other studies in the region, we found that most injured children were pedestrians [ 30 31 32 ]. We suspect that children are vulnerable to traffic accidents while playing or going to and returning from school, a hypothesis supported by a study in Tanzania [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…Road traffic accidents are a common cause of injury for both children and adults in sub-Saharan Africa [ 29 ]. Similar to other studies in the region, we found that most injured children were pedestrians [ 30 31 32 ]. We suspect that children are vulnerable to traffic accidents while playing or going to and returning from school, a hypothesis supported by a study in Tanzania [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…To determine the number of injuries assigned to each injured person, we developed a negative exponential distribution and calibrated our resulting average number of injuries reported in a paediatric study from Malawi’s Kamuzu Central Hospital (Sundet et al 2018 ). Our process of developing the distribution is given in ‘ Appendix ’.…”
Section: Methodsmentioning
confidence: 99%
“…We tried to account for this uncertainty by running the model for varying parameter values which produced an overall percentage of HSB falling within the range reported by Zafar et al (2018). In each of these runs the number of injuries and probability of death in-hospital was adjusted to still match the results of studies from KCH (Tyson et al 2015;Sundet et al 2018), a consequence of this calibration effort was in different model runs, a person with the same injuries would have a slightly different likelihood of mortality. This run-speci c calibration was necessary as there wasn't a Malawi-speci c estimate for HSB, but without a set point to calibrate to, we were limited in our investigation of the interaction between road tra c injury epidemiology, HSB and health system usage.…”
Section: Discussionmentioning
confidence: 99%
“…The GBD estimates were the only population wide estimate for the incidence of RTIs in Malawi that also provided an estimate for the incidence of death, as such, the results of our model are dependent on the validity of the GBD estimates. We also based our model's predicted number of injuries on results from a study focusing on paediatric patients (Sundet et al 2018).…”
Section: Modelling Discussionmentioning
confidence: 99%
See 1 more Smart Citation